Scapulothoracic muscle activity during elevation exercises measured with surface and fine wire EMG: A comparative study between patients with subacromial impingement syndrome and healthy controls. (June 2016) - Castelein, Birgit; Cagnie, Barbara; Parlevliet, Thierry; Cools, Ann
Abstract: Background: The quality of the scapular movement depends on the coordinated activity of the surrounding scapulothoracic muscles. Besides the well-known changes in Trapezius and Serratus Anterior (SA) activity in patients with subacromial impingement syndrome (SIS), no studies exist that have investigated the activity of the smaller less superficial muscles that attach on the scapula (Pectoralis Minor (Pm), the Levator Scapulae (LS) and the Rhomboid Major (RM)) in a population with SIS, despite the hypothesized importance of these muscles in shoulder function. Objectives: To investigate if patients with shoulder impingement syndrome (SIS) show differences in deeper and superficial lying scapulothoracic muscle activity in comparison with a healthy control group during arm elevation tasks. Study design: Controlled laboratory study. Methods: Activity of the deeper lying (LS, Pm and RM) and superficial lying scapulothoracic muscles (Trapezius and SA) was investigated with fine-wire and surface electromyography (EMG) in 17 subjects with SIS and 20 healthy subjects while performing 3 elevation tasks: scaption, wall slide and elevation with external rotation. Possible differences between the groups were studied with a linear mixed model (factor "group" and "exercise"). Results: For the Pm only, a significant main effect for "Group" was found: during the elevation exercises, the Pm was significantly more active in the SIS group in comparison with the healthy controls. Conclusion: Patients with SIS show significantly higher Pm activity during elevation tasks in comparison with healthy controls. This study supports the idea of a possible role of the Pm in SIS. Highlights: Significantly higher Pm activity was found in patients with SIS during elevation. No differences were found for other scapulothoracic muscles in patients with SIS. This study supports the idea of a possible role of Pm in patients with SIS.